Practical implementation of the concept of "Culture of Health" in the process of physical education teachers. - Verbludov I.B; Cudrenko A.I; Chochura N.D (Kharkov National Pedagogical University, 2011)
The article explains the usefulness and methodology of the use of psychotherapy in the formation of inner psycho-physiological mechanisms of personality that characterize the concept of "Culture of Health". Also, the article highlights the use of extra-curricular activities for physical education students of pedagogical universities to address problem. In experiment took part 178 male and female students.